Luigi Dallapiccola's 'New Antiquity'. Analysis of the Tartiniana Seconda MR58a (Ex Chordis, 2023)
The aim of this paper is to analyse Tartiniana Seconda MR58a for violin and piano by Luigi Dallapiccola (1904-1975). The piece is on the topic of re-writing the instrumental Italian music, and it borrows its themes from the Sonata VII B.a1 by Giuseppe Tartini (1692-1770). Moreover, both Dallapiccola and Tartini were born in the same land. Dallapiccola uses counterpoint and serial techniques to re-write the tartinian themes, creating a violin line that shares many virtuosities with the original Sonata VII, and a piano line that is not a simple accompaniment, but linked to the first one. Our analysis is inspired by Sandro Perotti and his research tips about re-writings; moreover, the form, canons, harmonic syntax and motivic elements are alnalysed, with some diagrams to resume the mathematical constructions of Dallapiccola’s writing.
Keywords: Luigi Dallapiccola; Giuseppe Tartini; Re-writings; Music Analysis; Neoclassicism